Effect of fat contents of buttermilk on fatty acid composition, lipolysis, vitamins and sensory properties of cheddar-type cheese - Asif, Mussab; Nadeem, Muhammad; Imran, Muhammad; Ullah, Rahman; Tayyab, Muhammad; Khan, Faima Atta; Al-Asmari, Fahad; Rahim, Muhammad Abdul; Rocha, João Miguel; Korma, Sameh A.; Esatbeyoglu, Tuba (Frontiers in Microbiology, 2023)
Cheddar-type cheese produced from buttermilk had softer texture than standard cheddar cheese due to lower fat content of buttermilk. Fat is extremely important for the functional characteristics and optimum textural attributes of cheese. The effect of different fat contents of buttermilk on chemical characteristics of cheddar-type cheese is not previously investigated. This investigation was conducted to know the effect of different fat contents of buttermilk on fatty acids composition, organic acids, vitamins, lipolysis and sensory characteristics of cheddar-type cheese. Cheddar-type cheese was produced from buttermilk having 1, 1.75, 2.50 and 3.25% fat contents (control, T1, T2 and T3). Fat content of control, T1, T2 and T3 were 9.81, 16.34, 25.17 and 31.19%. Fatty acids profile was determined on GC-MS, organic acids and vitamin A and E were determined on HPLC. Free fatty acids, peroxide value and cholesterol were determined. Cheddar-style cheese produced from buttermilk (1% fat) showed that it had softer texture and lacking typical cheese flavor. Gas chromatography–mass spectrometry (GC-MS) analysis showed that long-chain unsaturated fatty acids in control, T1, T2 and T3 samples were 45.88, 45.78, 45.90 and 46.19 mg/100g. High Performance Liquid Chromatography (HPLC) analysis showed that lactic acid, propionic acid, citric acid and acetic acid gradually and steadily increased during the storage interval of 90 days. At the age of 90 days, lactic acid in control, T1, T2 and T3 was 4789, 5487, 6571 and 8049 ppm respectively. At the end of ripening duration of 90 days, free fatty acids in control, T1, T2 and T3 were 0.29, 0.31, 0.35 and 0.42% with no difference in peroxide value. Stability of vitamin A after 90 days storage control, T1, T2 and T3 was 87.0, 80.0, 94.0 and 91.0%. Flavor score of cheddar-type cheese produced from butter milk having 1.0, 2.5 and 3.25% fat content was 81, 89 and 91% of total score (9). Hence, it is concluded that cheddar-type cheese can be produced from buttermilk having 2.5% and 3.25% fat contents with acceptable sensory attributes. Application of buttermilk for the production of other cheese varieties should be studied.